2020
DOI: 10.1007/s42452-020-2070-3
|View full text |Cite
|
Sign up to set email alerts
|

The recent advances in the mathematical modelling of human pluripotent stem cells

Abstract: Human pluripotent stem cells hold great promise for developments in regenerative medicine and drug design. The mathematical modelling of stem cells and their properties is necessary to understand and quantify key behaviours and develop non-invasive prognostic modelling tools to assist in the optimisation of laboratory experiments. Here, the recent advances in the mathematical modelling of hPSCs are discussed, including cell kinematics, cell proliferation and colony formation, and pluripotency and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 118 publications
(238 reference statements)
0
19
0
Order By: Relevance
“…ABM provides a multiscale investigation of a system as a direct observation can be made on individual cells while the cumulative results are captured at the population level [19] , [20] , [21] . ABM has been widely used in the literature to study cellular responses [15] , [17] , [18] . A common challenge in ABM is the abstraction of cellular behavior which requires an algorithm to correctly govern the decision-making process [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABM provides a multiscale investigation of a system as a direct observation can be made on individual cells while the cumulative results are captured at the population level [19] , [20] , [21] . ABM has been widely used in the literature to study cellular responses [15] , [17] , [18] . A common challenge in ABM is the abstraction of cellular behavior which requires an algorithm to correctly govern the decision-making process [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Such an algorithm receives cellular inputs at the microscale and predicts cellular behavior. Several approaches have been proposed in the literature to simulate the decision-making process such as simple rule definition, differential equations, logic-based approach, and artificial neural networks [15] , [24] , [25] , [26] . Fuzzy logic (FL)-based have shown great potential in resolving technical barriers between experimental and simulation experts thanks to its plain language [27] .…”
Section: Introductionmentioning
confidence: 99%
“…For over a last few decades, various studies indicated the pertinence of miRNAs biology in cancer, showing that they can behave both as oncogenes and tumor repressors; negatively regulating the protein-coding oncogenes [6,7]. Many researchers have dictated that miRNAs can influence cancer phenotypes and many reports have exhibited miR-NAs expression profiles which provide detail about tumor origin, prognosis and diagnosis of cancer [8].…”
Section: Microrna Discoverymentioning
confidence: 99%
“…However, careful, experiment-based quantification of the stochastic, temporal dynamics of PTFs is necessary to examine the resulting effects on cell fate. Statistical analysis and mathematical modelling are deepening our understanding of hPSC behaviours and guiding the development of experimental protocols [21]. Recent mathematical models of cell pluripotency focus on describing the network of PTFs and the resulting cell fate decisions to guide the optimisation and control of pluripotency February 26, 2021 2/37 in-vitro [21][22][23].…”
Section: Introductionmentioning
confidence: 99%